A randomized phase 1 study of the safety and immunogenicity of 2 novel pneumococcal conjugate vaccines in healthy Japanese adults in the United States. Issue 7 (3rd July 2021) - Fitz-Patrick, David; Young Jr, Mariano; Scott, Daniel A.; Scully, Ingrid L.; Baugher, Gary; Peng, Yahong; Jansen, Kathrin U.; Gruber, William; Watson, Wendy
ABSTRACT: Expanding serotype coverage of pneumococcal conjugate vaccines (PCVs) to target prevailing disease-causing serotypes could further reduce disease burden. To address this need, 2 different PCVs have been investigated: a 20-valent PCV (PCV20; includes the 13 serotypes in the 13-valent PCV [PCV13] plus 7 additional serotypes [8, 10A, 11A, 12F, 15B, 22F, 33F]) and a complementary 7-valent PCV (cPCV7; contains only the 7 additional serotypes). This phase 1b, randomized, controlled, double-blind study evaluated PCV20 and cPCV7 safety and immunogenicity in healthy Japanese adults 18–49 years of age residing in the United States for ≤5 years. Participants (n = 104) were randomized equally to receive a single dose of PCV20, cPCV7, or PCV13. Immunogenicity was assessed at baseline and 1 month after vaccination using serotype-specific opsonophagocytic activity (OPA) titers and serotype-specific immunoglobulin G (IgG) concentrations. Prompted local reactions and systemic events; adverse events (AEs); and serious AEs and newly diagnosed chronic disease were assessed 14 days, through 1 month, and upto 6 months following vaccination, respectively. OPA immune responses were robust for all 20 serotypes in the PCV20 group and for the 7 serotypes in the cPCV7 group 1 month after vaccination. IgG immune response showed similar trends. Injection site pain and muscle pain were the most common local reaction and systemic event; the majority were mild or moderate in severity. Few AEs and no severe AEs, serious AEs, or safety-related withdrawals were reported. Taken together, administration of PCV20 or cPCV7 in Japanese adults was well tolerated and induced robust serotype-specific functional immune responses. NCT03642847.